From ark to bank: extinction, proxies and biocapitals in ex-situ biodiversity conservation practices. Issue 1 (2nd January 2020) - Breithoff, Esther; Harrison, Rodney
ABSTRACT: This paper takes a critical approach to understanding the social and cultural 'work' of natural heritage conservation, focussing specifically on ex-situ biodiversity cryopreservation practices. Drawing on ethnographic fieldwork with the Frozen Ark, a UK-based 'frozen zoo' aiming to preserve the DNA of endangered animal species, the paper situates the development of non-human animal biobanks in relation to current anxieties regarding the anticipated loss of biodiversity. These developments are seeding new global futures by driving advances in technologies, techniques and practices of cloning, de-extinction, re-wilding and potential species re-introduction. While this provides impetus to rethink the nature of 'nature' itself, as something which is actively made by such conservation practices, we also aim to make a contribution to the development of a series of critical concepts for analysis of ex-situ and in-situ natural heritage preservation practices, which further illuminates their roles in building distinctive futures, through discussion of the relationship between conservation proxies, biobanking and biocapitals. We suggest that questions of value and the role of future making in relation to heritage cannot be disassociated from an analysis of economic issues, and, therefore, the paper is framed within a broader discussion of the place of ex-situ biodiversity cryopreservation in the late capitalist global economy.